A novel Li+-doped CsCu2I3 single crystal for dual gamma–neutron detection. Issue 1 (9th December 2022) - Liu, Dongdong; Wei, Qinhua; Tong, Yufeng; Xiang, Peng; Cai, Peiqing; Tang, Gao; Shi, Hongsheng; Qin, Laishun
Abstract : Study on the growth of a Li + -doped CsCu2 I3 crystal for dual gamma-ray and neutron detection. Abstract : Halide perovskites are among the most attractive research hotspots in optoelectronic applications due to their excellent luminescence properties. In this paper, Li + was successfully incorporated into a one-dimensional perovskite CsCu2 I3 host and constructed as a novel neutron/gamma detection scintillator via the Bridgman method. XRD and ICP-MS were carried out, and the results were discussed. The Li-doped CsCu2 I3 crystal exhibits a main emission peak at 575 nm originating from strongly localized 1D exciton emission and a high photoluminescence quantum efficiency of 18.7%. The CsCu2 I3 :Li crystal has a light yield of 10 900 photons per MeV and an energy resolution of 11.5% under 137 Cs irradiation. The figure-of-merit (FoM) of the CsCu2 I3 :Li crystal has been estimated (about 0.8) under 252 Cf radiation source. The crystal has a potential application for dual gamma–neutron detection.